АЛГОРИТМ РОБАСТНОГО ПРЯМОГО ВЕКТОРНОГО КЕРУВАННЯ АСИНХРОННИМ ГЕНЕРАТОРОМ - Пересада, С.М.; Божко, С.В.; Ковбаса, С.М.; Ніконенко, Є.О. (Інститут електродинаміки НАН України, Київ, 2021)
A novel and robust field oriented vector control method for standalone induction generators (IG) is presented. The proposed controller exploits the concept of direct field orientation and provides asymptotic rotor flux modulus and DC-link voltage regulations when a DC-load is constant or slowly varying. Flux subsystem, designed using Lyapunov’s second method, has, in contrast to standard structures, closed loop properties and therefore is robust with respect to rotor resistance variations. A decomposition approach on the base of the two-time scale separation of the voltage and torque current dynamics is used for design of the voltage subsystem. The feedback linearizing voltage controller is designed using a steady state IG power balance equation. The resulting quasi-linear dynamics of the voltage control loop allows use of simple controllers tuning procedure and provides an improved dynamic performance for variable speed and flux operation. Results of a comparative experimental study with standard indirect field oriented control are presented. In contrast to existing solutions, the designed controller provides system performances stabilization when speed and flux are varying. It is experimentally shown that a robust field oriented controller ensures robust flux regulation and robust stabilization of the torque current dynamics leading to improved energy efficiency of the electromechanical conversion process. The proposed controller is suitable for energy generation systems with variable speed operation. References 18, figures 8.